Se7en car Accessories / Aian Joy Albaran ... [et al.] - Albaran, Aian Joy; Thomas, Christopher Jerry; Livining, Christopher Steve; Kuntong, Jerry Jiling; Abu Bakar, Maizatul Husna; Rauf, Mohd Azim; Benignus, Valerian (2015)
Se7en Car Accessories provide variety types of car accessories including a installation service to our customers. We are a newly formed business under partnership that established on 2015. Our business is located at Inanam, Sabah and we're targeting the people in that area as our potential customers. The focus in this business plan will be our "Anti Collision Laser Mark" that we newly produced with objective to reduce the car accident rate in Sabah. Based on our observation, the rate of accident in Sabah are increasing and we aimed to reduce that number by introducing our new invented product in the market. The laser lamp will help the drivers during the hazy, foggy or rainy day to have a clear vision about the car in front of them so that collision won't easily happened. We're invented this new product with expectation that our user will experience benefits from the laser mark. It brings a lot of benefits especially to those who drive long distance in the area that have a chance of foggy and hazy. Our Anti Collision Laser Mark has been acknowledge and approved by the government for its benefits to the user. This is to ensure and convince the public to use our product.